Hard or Soft? Institutional Reforms and Infrastructure Spending as Determinants of Foreign Direct Investment in China - K. C. Fung; Alicia Garcia-Herrero; Hitomi Iizaka; Alan Siu (University of California, Economics Department, 2005)
In this paper, we examine whether hard infrastructure in the form of more highways and railroads or soft infrastructure in the form of more transparent institutions and deeper reforms lead to more foreign direct investment (FDI). We use data of FDI from the United States, Japan, Hong Kong, Taiwan and Korea to various regions of China from 1990 to 2002. We control for the standard determinants of FDI - regional market sizes, wage rates, human capital and tax policies. Then we add indices of hard and soft infrastructures. We found that empirically soft infrastructure consistently outperforms hard infrastructure as a determinant of FDI.
Keywords: 330